Application of The Law to Criminal Acts of Collective Destruction of Goods in The Students - Fernando, Youngky (PDPI (Perkumpulan Dosen Peneliti Indonesia), 2022)
The aim of this research is to determine the application of the law to criminal acts of property damage in Case number 1237/PID.B/2020/PNBGR. And obstacles in implementing the law against perpetrators acting in the name of students in demonstrations. This research method includes surveys, direct interviews, documentation studies. Data collection techniques include primary data, secondary and tertiary data. Describes a detailed description of the Application of Law to the Criminal Act of Damaging Property by Provocateurs in the Name of Students in Bogor. Case Number 1237/Pid.B/2020/Pn Bgr. The respondents in this research were Bogor District Court Judges, Bogor District Court Registrars, Students. Conclusion in the application of criminal law by the Panel of Judges at the Bogor District Court in Case number 1237/PID.B/2020/PNBGR which stated that the defendant was legally and convincingly proven guilty of committing a criminal act with joint force in public. Obstacles in implementing the law against perpetrators who act in the name of students in case number 1237/PID.B/2020/PNBGR do not understand the law in depth, so that the way of conveying these aspirations goes off track which results in being caught in the law, having a critical social environment for students, not having permanent job, so they have free time so they can take part in demonstrations.